The Association of Lipids and Lipoproteins with Hip Fracture Risk the Cardiovascular Health Study. - Barzilay, Joshua I; Bůzková, Petra; Kuller, Lewis H; Cauley, Jane A; Fink, Howard A; Sheets, Kerry; Robbins, John A; Carbone, Laura D; Elam, Rachel E; Mukamal, Kenneth J (Am J Med, 2022)
BACKGROUND: It is uncertain if lipids or lipoproteins are associated with osteoporotic fractures. In this study, incident hip fracture risk according to conventional lipid levels and lipoprotein levels and sizes was examined. METHODS: We followed 5832 participants aged ≥65 years from the Cardiovascular Health Study for hip fracture for a mean of 13.5 (SD 5.7) years. Standard enzymatic methods were used to determine lipid levels (HDL-c, LDL-c, triglycerides). Nuclear magnetic resonance spectroscopy was used to measure lipoprotein fractions (VLDL-P, LDL-P, HDL-P) in a subset of 1849 participants. RESULTS: We documented 755 incident hip fractures among women (1.19 fractures per 100 participant years [95% CI, 1.04, 1.35]) and 197 among men (0.67 fractures per 100 participant years [95% CI, 0.41, 1.10]) over an average follow-up. HDL-c and LDL-c levels had statistically significant non-linear U-shaped relationships with hip fracture risk (HDL-c, p=0.009; LDL-c, p=0.02). Triglyceride levels were not significantly associated with hip fracture risk. In fully adjusted conjoint models, higher VLDL-P concentration [HR per 1-standard (SD) increment 1.47 (1.13, 1.91)] and size [HR per 1-SD increment 1.24 [1.05, 1.46]) and higher HDL-P size (HR per 1-SD increment 1.81 [1.25, 2.62]) were all associated with higher hip fracture risk. CONCLUSIONS: Lipids and lipoproteins are associated with hip fracture risk in older adults. The associations are complex. Mechanistic studies are needed to understand these findings.

The associations of markers of endothelial dysfunction with hip fracture risk. - Barzilay, Joshua I; Bůzková, Petra; Fink, Howard A; Cauley, Jane A; Carbone, Laura; Elam, Rachel; Robbins, John A; Stein, Phyllis; Sheets, Kerry; Jalal, Diana; Mukamal, Kenneth J (Arch Osteoporos, 2023)
UNLABELLED: Endothelial dysfunction underlies the development of atherosclerotic vascular disease, which in turn is associated with osteoporotic fractures. Here, we examined the association of two markers of endothelial dysfunction with incident hip fracture risk in older adults but found no statistically significant associations between them. PURPOSE/INTRODUCTION: Endothelial dysfunction underlies the development of atherosclerotic vascular disease. Vascular disease, in turn, is associated with the risk of osteoporotic fractures, such as hip fractures. Here, we examine whether two measures of endothelial dysfunction are related to hip fracture risk. METHODS: Participants for this study were 2792 individuals (mean age 78.6 years) who had flow-mediated dilation (FMD) measured after ischemia in the forearm and 2255 adults (mean age 73.3 years) with measured soluble intercellular adhesion molecule (siCAM) levels, a constitutive endothelial cell membrane protein associated with the initiation of atherosclerosis. Mean follow-up was 9.7 and 11.7 years, respectively. There were 375 and 265 incident hip fractures, respectively, in each group. RESULTS: In Cox proportional hazards models, there was no significant association between FMD response and incident hip fracture (HR per 1% higher FMD was 0.98 [0.93, 1.04]; p = 0.44). In exploratory analyses, when data were examined dichotomously, participants in the lowest 80% of FMD (≤ 4.5%) had an adjusted 1.29 (0.98, 1.68; p = 0.067) higher hazard of hip fracture compared to participants in the upper 20% of FMD change. There were no significant associations between siCAM and incident hip fracture whether examined as a continuous or dichotomized variable. CONCLUSIONS: Among older adults, two measures of endothelial dysfunction were not significantly associated with hip fracture risk. There was a trend for higher fracture risk with lower FMD.
Keywords: Aged; Forearm; Hip Fractures; Humans; Osteoporotic Fractures; Vascular Diseases

Mortality Following Hip Fracture in Older Adults With and Without Coronary Heart Disease. - Robbins, John A; Bůzková, Petra; Barzilay, Joshua I; Cauley, Jane A; Fink, Howard A; Carbone, Laura D; Chen, Zhao; Stein, Phyllis K; Elam, Rachel; Sheets, Kerry; Mukamal, Kenneth J (Am J Med, 2023)
BACKGROUND: Comorbidities like coronary heart disease are common among older people who sustain an osteoporotic hip fracture. However, their impact on short- and long-term mortality post-hip fracture is not well quantified. METHODS: We examined 4092 and 1173 older adults without and with prevalent coronary heart disease, respectively. Post-hip fracture mortality rates were computed with Poisson models and hazard ratios with Cox regression. For perspective, we compared mortality rates among participants with prevalent coronary heart disease who had either a hip fracture or incident heart failure (but no hip fracture). RESULTS: Among participants without prevalent coronary heart disease, the mortality rate post-hip fracture was 21.83 per 100 participant years, including 49.27 per 100 participant years in the first 6 months following hip fracture. Among participants with prevalent coronary heart disease, the corresponding mortality rates were 32.52 and 79.44 per 100 participant years, respectively. Participants with prevalent coronary heart disease and incident heart failure (but no hip fracture) had corresponding post-incident heart failure mortality rates per 100 participant years of 25.62 overall and 46.4 in the first 6 months. In all 3 groups, the hazard ratio for mortality was similarly elevated: 5- to 7-fold at 6 months and 1.7- to 2.5-fold beyond 5 years. CONCLUSION: As a case study in the absolute effects of a comorbidity on post-hip fracture mortality, hip fracture in a person with coronary heart disease carries an exceedingly high mortality rate, even higher than that following incident heart failure in individuals with coronary heart disease.